Increased number of Judo therapy facilities in Japan and changes in their geographical distribution - Nomura Kyoko; Nakao Mutsuhiro; Inoue Satoshi; Yano Eiji (BMC, 2011)
Abstract Background Judo therapy is a well established Japanese co-medical profession specializing in outpatient manual treatment of fractures and sprains. Recently, the number of judo therapists has been rapidly increasing as a result of proliferation judo therapy academies. This study examines whether such rapid increases have improved geographical distribution of judo therapy facilities in Japan. Methods The number of judo therapy facilities and the population in each municipality were obtained from the Web yellow pages and from Japanese census data for 2004, 2006, and 2008, respectively. Lorenz curves and Gini indices were calculated to demonstrate distributions of judo therapy facilities per 100,000 people. A bootstrapped method was used to identify statistical significances of differences in Gini indices. Results In all municipalities, the mean numbers of judo therapy facilities per 100,000 people were 15.3 in 2004, 15.8 in 2006, and 17.6 in 2008. The Gini indices for judo therapy facilities nationally were 0.273 in 2004, 0.264 in 2006, and 0.264 in 2008. The numbers of judo therapy facilities increased significantly between 2006 and 2008 (p < 0.05) but the indices did not change significantly in the same period. The Gini indices for local towns and villages remained unchanged and were consistently higher (p < 0.05) than those in urban areas throughout the study periods. Conclusion Our results suggest that recent increases in the number of judo therapy facilities have not necessarily led to greater equality in their geographic distribution in terms of Gini indices.